Toxicological assessment of novel Anti-COVID traditional Chinese medicine formulae NRICM101 and NRICM102: a comprehensive study on safety and genotoxicity - Chiou, Chun-Tang; Chang, Chao-Lin; Tseng, Yu-Hwei; Liao, Geng-You; Liao, Jiunn-Wang; Shen, Yuh-Chiang; Wei, Wen-Chi; Tsai, Keng-Chang; Huang, Yu-Ching; Chang, Wen-Chiung; Chiou, Wen-Fei; Liaw, Chia-Ching; et al. (Frontiers in Pharmacology, 2025)
Although the first outbreak of COVID-19 occurred in 2019, the virus continues to circulate globally, even years later. In Taiwan, the novel traditional Chinese medicine formulas, NRICM101 and NRICM102, have been extensively used to treat COVID-19, with Chinese medicine practitioners frequently prescribing them to manage the disease. According to data from the Taiwan Centers for Disease Control, approximately 22% of COVID-19 patients opted for NRICMs’ treatments between 2021 and 2022. Despite the widespread use and reported effectiveness of these treatments, it is critical to evaluate the potential risks associated with their prolonged or frequent use. In this study, we conducted a comprehensive toxicological assessment of NRICM101 and NRICM102. Acute oral toxicity was evaluated by administering a single 5 g/kg bw dose to ICR mice and SD rats. No mortality, sex-related differences, or clinical signs of toxicity were observed. Subchronic toxicity was assessed through a 28-day repeated oral administration study with doses of 1.6, 3.1, and 4.8 g/kg bw per day of NRICM101 or 102, which showed no treatment-related deaths or organ pathology. While some hematological changes were noted, they were generally within physiological ranges and showed no consistent dose-dependent trends. Genotoxicity was assessed using three standard assays. The Ames test revealed no mutagenic activity. The in vitro mouse lymphoma assay showed genotoxicity only at the highest concentration (5.0 mg/mL) and only in the absence of S9 metabolic activation, suggesting a context-dependent response possibly linked to direct-acting or cytotoxic effects at excessive doses. In contrast, the in vivo micronucleus assay, which reflects systemic genotoxicity under physiologically relevant conditions, showed negative results. Together, these findings indicate that NRICM101 and NRICM102 are not associated with acute or subchronic toxicity at clinically relevant doses and durations, and they present a low genotoxic risk under standard conditions of use. Nonetheless, further long-term and pharmacokinetic studies are warranted to fully characterize their safety profiles, particularly with high-dose or prolonged administration.